Selecting native perennial plants for ecological intensification in Mediterranean greenhouse horticulture. Issue 5 (4th December 2017) - Rodríguez, E.; González, M.; Paredes, D.; Campos, M.; Benítez, E.
Abstract: Natural control by predators and parasitoids provides an important and often unnoticed ecosystem service to agricultural landscapes by reducing pest populations in crops. The current model of horticultural intensification in south-eastern Spain produces high yields but has also resulted in a landscape almost completely covered by plastic. Promoting natural areas among greenhouses could enhance biodiversity, by being beneficial insects, and reduce pest pressure outdoors. The first step is to ascertain how pests and their natural enemies (NEs) use Mediterranean vegetation for selecting the best plants for pest suppression outdoors. The abundance of the two major horticultural pests, the tobacco whitefly, Bemisia tabaci, and the western flower thrips, Frankliniella occidentalis, together with their NEs, were assayed in 22 flowering perennial plants, which were newly planted in an experimental field surrounded by greenhouses. Eight plant species were identified as the most critical species for sustaining pest populations outdoors. A set of five plant species supported a medium level of pests, and another set of ten plant species supported the lowest level of both pests. Tobacco whitefly occurred in a few plants species, whereas western flower thrips occurred on almost all the plant species studied, and was favoured by the presence of flowers in perennial plants. The results suggest that plant diversity may provide relatively few acceptable host plants for tobacco whitefly than for western flower thrips. NEs were generally collected in plants that also supported abundance of pests, indicating that host/prey availability, more than food resources from flowers, was a stronger predictor of NE abundance in perennial plants. Field trials using the plants with the lowest host acceptance by pests are needed in order to ascertain whether pest abundance outdoors is reduced.